Sri Lanka Poverty Update : Background Report to Sri Lanka Poverty Assessment - World Bank (World Bank, Washington, DC, 2021)
Sri Lanka has made strong progress in reducing poverty and sharing prosperity among the less well-off in recent years. The poverty rate using the World Bank's 3.20 Dollars poverty line (in 2011 purchasing power parity) declined from 16.2 percent in 2012/13 to 11 percent in 2016, a reduction that compares favorably to regional peers. Extreme poverty is almost eliminated. Gains were also made in nonmonetary measures of welfare, including access to basic services, housing conditions, and asset ownership. Growth was inclusive but less pro-poor: per capita consumption growth of the bottom 40 percent of the consumption distribution accelerated to an annualized 4.2 percent but was still below the population averageof 4.7 percent between 2012/13 and 2016. A significant increase in labor income, particularly from nonfarm sectors, is the major factor behind progress. The economy is steadily transitioning toward industry and services, and sectors such as construction and trade led job creation in recent years. Wage growth has also been strong. The expansion in services was underpinned by a booming tourism sector, as tourist arrivals quadrupled between 2009 and 2016. Real gross domestic product (GDP) growth was mainly driven by gains in labor productivity, though most of the productivity growth came from increases in within-sector productivity rather than from reallocation effects. This implies that most of the labor movement occurred from agriculture toward other sectors with low productivity. Agriculture did not contribute to poverty reduction as it had in the previous decade because stagnating productivity and a reversal of favorable prices slowed agricultural income growth.